TENSION AND DEFORMATIONS OF STAR-SHAPED SPRING VERTICES WITH STRANGULATED ENDS OF THE FLEXIBLE COUPLING (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article examines the structure of overload flexible coupling that contains internal and external hubs, connected by a star-shaped spring with the circular vertices inserted in grooves on the outer surface of internal hub and inner surface of the external hub. Position of the star-shaped spring is fixed on the inner hub by the wedge, which allows the spring to be made either solid or of separate circular vertices with strangulated ends. Geometric synthesis of star-shaped spring with vertices of circular shape, depending on its size was conducted. It is assumed that star spring vertices are the double-hinge arches of circular form. Calculations of analytical solutions using the methods of structural mechanics were done. Analytical expressions proved workability of the star-shaped spring of flexible overload coupling during the torque transmission.
Keywords: flexible overload coupling; star-shaped spring; circular vertices; statics calculation; deformation